STUDENTS’ PERCEPTIONS OF THE USE OF ARTIFICIAL INTELLIGENCE IN COMPLETING MATHEMATICS ASSIGNMENTS - Afianti, Delima; Laswadi, Laswadi (Jurnal Pendidikan Matematika dan IPA, 2026)
The use of Artificial Intelligence (AI) in education has brought attention to how students view its role in helping them complete mathematics tasks. This study explores these perceptions by considering seven indicators: cognitive, affective, conative, usefulness, ease of use, critical awareness, and independence versus dependence. The research employed a descriptive quantitative design involving 33 Mathematics Education students at IAIN Kerinci. Data were gathered through a Likert-scale questionnaire and processed using descriptive statistical techniques. The results indicate that students tend to have positive perceptions, reflected in a mean score of 3.3470. While AI is generally seen as useful and easy to operate, some students still express concerns about becoming too dependent and losing opportunities to learn independently. These findings point to the need for instructional approaches that utilize AI wisely while still fostering critical, ethical, and independent learning habits.